Clinical features and treatment of nonalcoholic fatty liver disease across the Asia Pacific region-the GO ASIA initiative - Chan, Wah Kheong; Treeprasertsuk, Sombat; Imajo, Kento; Nakajima, Atsushi; Seki, Yousuke; Kasama, Kazunori; Kakizaki, Satoru; Fan, Jian Gao; Song, Myeong Jun; Yoon, Seung Kew; Dan, Yock Young; Lesmana, Laurentius; et al. (Wiley, 2018)
Background: The Gut and Obesity Asia (GO ASIA) workgroup was formed to study the relationships between obesity and gastrointestinal diseases in the Asia Pacific region. Aim: To study factors associated with nonalcoholic steatohepatitis (NASH) and advanced fibrosis, and medical treatment of biopsy-proven nonalcoholic fatty liver disease (NAFLD) patients. Methods: Retrospective study of biopsy-proven NAFLD patients from centres in the GO ASIA Workgroup. Independent factors associated with NASH and with advanced fibrosis on binary logistic regression analyses in a training cohort were used for the development of their corresponding risk score, which were validated in a validation cohort. Results: We included 1008 patients from nine centres across eight countries (NASH 62.9%, advanced fibrosis 17.2%). Independent predictors of NASH were body mass index ≥30 kg/m2, diabetes mellitus, dyslipidaemia, alanine aminotransferase ≥88 U/L and aspartate aminotransferase ≥38 U/L, constituting the Asia Pacific NASH risk score. A high score has a positive predictive value of 80%-83% for NASH. Independent predictors of advanced fibrosis were age ≥55 years, diabetes mellitus and platelet count <150 × 109/L, constituting the Asia-Pacific NAFLD advanced fibrosis risk score. A low score has a negative predictive value of 95%-96% for advanced fibrosis. Only 1.7% of patients were referred for structured lifestyle program, 4.2% were on vitamin E, and 2.4% were on pioglitazone. Conclusions: More severe liver disease can be suspected or ruled out based on factors identified in this study. Utilisation of structured lifestyle program, vitamin E and pioglitazone was limited despite this being a cohort of biopsy-proven NAFLD patients with majority of patients having NASH.